Answer:
The answer is
Step-by-step explanation:
Step by step
The answer is a = 0, b = -5, and c= 39.
<u>Step-by-step explanation</u>:
<u>step 1</u> :
A quadratic equation means that it should have at least one squared term.
<u>step 2</u> :
The standard form is ax² + bx + c = 0.
<u>step 3</u> :
The solution to the quadratic equation is usually written in the form
x = (-b ± √(b2 − 4ac))/(2a)
where a = coefficient of x^2
b = coefficient of x
c = constant term
<u>step 4</u> :
The given equation is -5x +32.
∴ The answer is a = coefficient of x^2 = 0
b = coefficient of x = -5
c = constant term = 39
Answer:
![\frac{(6q-5)}{(3q+5)}](https://tex.z-dn.net/?f=%5Cfrac%7B%286q-5%29%7D%7B%283q%2B5%29%7D)
Step-by-step explanation:
Given: ![\frac{18q^{2}-45q+25 }{9q^{2}-25 }](https://tex.z-dn.net/?f=%5Cfrac%7B18q%5E%7B2%7D-45q%2B25%20%7D%7B9q%5E%7B2%7D-25%20%7D)
Factorizing the numerator and the denominator, we have:
18
- 45q + 25 = 18
- 30q - 15q + 25
= (3q - 5)(6q - 5)
and
9
- 25 = (3q - 5)(3q + 5)
So that,
= ![\frac{(3q-5)(6q-5)}{(3q-5)(3q+5)}](https://tex.z-dn.net/?f=%5Cfrac%7B%283q-5%29%286q-5%29%7D%7B%283q-5%29%283q%2B5%29%7D)
= ![\frac{(6q-5)}{(3q+5)}](https://tex.z-dn.net/?f=%5Cfrac%7B%286q-5%29%7D%7B%283q%2B5%29%7D)
Therefore,
=